2013
DOI: 10.3945/ajcn.112.039065
|View full text |Cite
|
Sign up to set email alerts
|

Functional glycans and glycoconjugates in human milk

Abstract: Human milk contains complex carbohydrates that are important dietary factors with multiple functions during early life. Several aspects of these glycostructures are human specific; some aspects vary between lactating women, and some change during the course of lactation. This review outlines how variability of complex glycostructures present in human milk is linked to changing infants' needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 143 publications
0
36
0
Order By: Relevance
“…Milk composition varies greatly across mammalian species, as an adaptation to environment and nutrient requirements of the different mammalian infants [2,3]. Only the sea lion and the marsupialslargely inhabitants of the Pacific Ocean, are known to have milk without lactose, and still their first pouch milk is a trisaccharide of galactose [4].…”
Section: Galactose In Milkmentioning
confidence: 99%
“…Milk composition varies greatly across mammalian species, as an adaptation to environment and nutrient requirements of the different mammalian infants [2,3]. Only the sea lion and the marsupialslargely inhabitants of the Pacific Ocean, are known to have milk without lactose, and still their first pouch milk is a trisaccharide of galactose [4].…”
Section: Galactose In Milkmentioning
confidence: 99%
“…The nondigestibility of the scGOS+lcFOS mixture implies, in principle, ample opportunity of direct interaction with the digestive tract's surface as described by Georgi et al elsewhere in this supplement (88). With regard to the direct physical interaction of prebiotics as reviewed by Jeurink et al (89), it has been shown, for HMOSs, that these can directly modulate the function of immune cells (90,91).…”
Section: Modulation Of Gastrointestinal Physiology By Colonic Fermentmentioning
confidence: 99%
“…HMOSs and other NDOSs have been reported to bind to specific receptors on cells of the immune system as summarized by Georgi et al (88) and others (90,(131)(132)(133). Furthermore, in vitro evidence has been obtained for the epithelial transport of HMOSs (131).…”
Section: The Modulation Of Early-life Microbiota Correlates With Imprmentioning
confidence: 99%
“…complex oligosaccharides free or covalently bound (glycolipids, glycoproteins, glycopeptides, and glycosaminoglycans), have been observed both between lactating women and during the course of lactation, according to the newborn's needs. These complex glycostructures are important dietary factors during early life as they regulate multiple functions [88]. However, the growth rate of breast-fed babies is related to the total amount of milk they consume, rather than the concentration of fat, protein, or lactose [89].…”
Section: Milk Compositionmentioning
confidence: 99%